Clock synchronization method for micro-power wireless networks based on LoRa ranging. Issue 1 (1st November 2022) - Ren, Zhendong; Zhou, Ying; Wang, Hongmian; Sun, Xitong
Abstract: To measure various electrical parameters of power supply equipment, many sensors are installed near the low-voltage distribution transformers. Clock synchronization of the electrical parameters is important for functions such as data statistics and equipment fault location. This paper introduces the characteristics of LoRa and SX1280 architecture and the timing principle. On such a basis, timing error sources and elimination methods are studied. A clock synchronization method is proposed based on the ranging function. With typical test data, the hardware and software schemes are presented.